E-Learning - Tiwari, Kiran (Qualitative and Quantitative Methods in Libraries; Vol 7 No 1 (2018): March 2018 Issue, 2019)
This Paper provides a portrait overview of the use of e‐resources amongst concerning Indian DELNET associates LIS professional. E‐resources are progressively important to all aspects of education from teaching and learning, through to the collection of student data, Administration and marketing activities those institutions engage in. For this research e-resources are defined in the extensive sense and includes Virtual Learning Environments (VLEs), platforms, research software, and other e-resources (such as social networking technologies, use of Web 2.0 technologies, mobile phones or Audio Visual technologies) as they relate to systems used to aid learning, teaching and administration. The findings confirm the importance of e‐resources to the institutions, as they are used daily by staff in all areas of their work. One of our main findings was that the use of e‐resources within institutions is extremely varied, and often the most innovative uses and users are not supported centrally. Indeed, in many institutions there is a lack of communication between IT service departments and other personnel who are responsible for the pedagogical aspects of e-learning. Instead, innovative use and good practice often comes from individual academic or support staff who can be seen as “champions” for e-resources who introduce these initiatives. It is clear from the findings that e-resources and e-resource use is often not disseminated widely enough throughout individual institutions. As institutions have developed e-learning strategies and units, this may well be overcome in the short term, and these personnel will be able to oversee the roll-out of new e- learning innovations, be able to help with the dissemination of findings, and help to train staff in the use of these technologies.